Neo-cartilage engineered from primary chondrocytes is epigenetically similar to autologous cartilage, in contrast to using mesenchymal stem cells. Issue 8 (August 2016) - Bomer, N.; den Hollander, W.; Suchiman, H.; Houtman, E.; Slieker, R.C.; Heijmans, B.T.; Slagboom, P.E.; Nelissen, R.G.H.H.; Ramos, Y.F.M.; Meulenbelt, I.
Summary: Objectives: To compare the epigenetic landscape of 3D cell models of human primary articular chondrocytes (hPACs) and human bone-marrow derived mesenchymal stem cells (hBMSCs) and their respective autologous articular cartilage. Design: Using Illumina Infinium HumanMethylation450 BeadChip arrays, the DNA methylation landscape of the different cell sources and autologous cartilage was determined. Pathway enrichment was analyzed using DAVID. Results: Principal Component Analysis (PCA) of methylation data revealed separate clustering of hBMSC samples. Between hBMSCs and autologous cartilage 86, 881 cytosine-phosphate-guanine dinucleotides (CpGs) (20.2%), comprising 3, 034 differentially methylated regions (DMRs; Δ β > 0.1; with the same direction of effect), were significantly differentially methylated. In contrast, between hPACs and autologous cartilage only 5, 706 CpGs (1.33%) were differentially methylated. Of interest was the finding of the transcriptionally active, hyper-methylation of a Cartilage Intermediate Layer Protein ( CILP ) annotated DMR (Δ β = 0.16) in PAC-cartilage, corresponding to a profound decrease in CILP expression after in vitro culturing of hPACs as compared to autologous cartilage. Conclusions: In vitro engineered neo-cartilage tissue from primary chondrocytes, hPACs, exhibits a DNA methylation landscape that is almost identical (99% similarity) to autologous cartilage, in contrast to neo-cartilage engineered from bone marrow-derived mesenchymal stem cells (MSCs). Although hBMSCs are widely used for cartilage engineering purposes the effects of these vast differences on cartilage regeneration and long term consequences of implantation, are not known. The use of hBMSCs or hPACs for future cartilage tissue regeneration purposes should therefore be investigated in more depth in future endeavors to better understand the consequences of the differential methylome on neo-cartilage.